Teaching and Learning Resources as Determinants of Academic Performance in Public Secondary Schools in Kuria East and Kuria West Sub-Counties, Kenya - Othoo, Hezekiah Adwar; Olel, Maureen A.; Gogo, Julius (American Journal of Social Sciences and Humanities, 2019)
The continued increase in enrolment in secondary schools has put pressure on the limited teaching and learning resources thus affecting the academic performance of the schools. This study sought to determine the influence of teaching and learning resources on academic performance of public secondary schools of Kuria East and Kuria West Sub counties. Objectives of the study were to establish the influence of the level of adequacy the level of utilization of teaching and learning resources on academic performance in Kuria East and Kuria West sub-counties. The study employed Descriptive survey research design. Saturated random sampling technique was used to select 36 principals nested at 40 while stratified random sampling was used to select 138 out of 345 teachers . Data was collected through questionnaires, document analysis guide and observation checklist. Quantitative data was analyzed using descriptive and inferential statistics involving percentages, mean and linear regression, qualitative data using content analysis. Findings indicated that adequacy of teaching and learning resources had significant effect on academic performance with a regression coefficient of 0.87 and utilization 0.28. The study recommended that the government should avail adequate teaching and learning resources in schools and the school management should foster optimal utilization of teaching and learning resources. Findings of the study may be useful to educational planners, policy makers, and educational managers to utilize teaching and learning resources efficiently and device measures to address shortages of the said resources in schools so as to improve academic performance and to academicians for research purposes.